Sodium-Glucose Cotransporter 2 Inhibitors and Heart Failure: A Bedside-to-Bench Journey - Cappetta, Donato; De Angelis, Antonella; Bellocchio, Gabriella; Telesca, Marialucia; Cianflone, Eleonora; Torella, Daniele; Rossi, Francesco; Urbanek, Konrad; Berrino, Liberato (Frontiers in Cardiovascular Medicine, 2021)
Type 2 diabetes mellitus and heart failure are multifactorial diseases sharing common risk factors such as obesity, hyperinsulinemia, and inflammation, with underlying mechanisms including endothelial dysfunction, inflammation, oxidative stress and metabolic alterations. Cardiovascular benefits of sodium-glucose cotransporter 2 (SGLT2) inhibitors observed in diabetic and non-diabetic patients are also related to their cardiac-specific, SGLT-independent mechanisms, in addition to the metabolic and hemodynamic effects. In the search of the possible underlying mechanisms, research campaign has been launched proposing varied mechanisms of action that include intracellular ion homeostasis, autophagy, cell death and inflammatory processes. Moreover, the research focus was widened towards cellular targets other that cardiomyocytes. At the moment, intracellular sodium level reduction is the most explored mechanisms of direct cardiac effects of SGLT2 inhibitors that mediate the benefits in heart failure in addition to glucose excretion and diuresis. The restoration of cardiac Na+ levels with consequent positive effects on Ca2+ handling can directly translate into improved contractility and relaxation of cardiomyocytes and have antiarrhythmic effects. In this review we summarize clinical trials, studies on human cells and animal models, that provide a vast array of data in support of the repurposing this class of antidiabetic drugs.